Development of the antipodal Vivaldi antenna for detection of cracks inside concrete members. Issue 7 (July 2015) - Moosazadeh, Mahdi; Kharkovsky, Sergey
ABSTRACT Ultrawide band (UWB) nondestructive testing and evaluation techniques can provide the detection of defects and damages in construction materials and members. The development of UWB antennas with proper dimensions and high performance for these systems is one of the major challenges. In this letter, an antipodal Vivaldi antenna (AVA) has been developed to be used in UWB techniques for nondestructive detection of cracks in concrete members. To obtain a desirable antenna performance including the wider impedance bandwidth, the higher directivity, and higher front‐to‐back ratio rectangular‐shaped slits (RSS) and a half‐circular‐shaped lens (HCSL) have been added in the design of a conventional tapered slot AVA. A parametric study on the dimensions of the slits is provided to optimize performance and size of the proposed antenna. The optimum size of the proposed antenna is 40 × 80 × 0.508 mm3, and it operates over the frequency range from 3.4–40 GHz. It is shown that the RSS increase impedance bandwidth especially at the lower frequencies. Directivity of the proposed antenna at higher frequencies has been increased by the HCSL. The feasibility of the proposed antenna for nondestructive evaluation of concrete members is demonstrated by investigation into its performance with concrete specimens possessing an air‐gap inside a concrete specimen. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1573–1578, 2015